Development of a conceptual auditing framework by integrating ISO 9001 principles within auditing. Issue 3 (12th December 2019) - Abuazza, Omran Ahmad; Labib, Ashraf; Savage, Barbara M.
Abstract : Purpose: The purpose of this paper is to develop a conceptual auditing framework (CAF), which can help the organizations that experience difficulties with current ISO 9001 auditing to achieve their desired benefits with regard to the auditing of conformance, performance, risk management and improvement collectively. Design/methodology/approach: A literature review was undertaken to identify the audit limitations and the program strategies that were reported in literature to overcome these limitations. The relevant audit standard (ISO 9001:2015) and guidelines (ISO 19011:2011 and ISO 19011:2018) have also been reviewed to determine the gap in relation to this purpose. Findings: Most of the previous suggestions to overcome the difficulties of the current ISO 9001 auditing were to focus on processes in addition to ISO 9001 clauses and to apply the two principles of "Process Approach" and "Improvement" of ISO 9001, by having the manner of integration of their risk-based thinking concept and Lean Six Sigma (LSS) approaches, respectively, within audit. However, this integration also has limitations such as the desire for implementing risk management program and the necessity for applying LSS approach. Therefore, a CAF was developed to enhance the ISO 9001 quality audit. It suggests the integration of 12 management tools that are connected to the seven principles of ISO 9001:2015 severally and collectively. The selected tools ought to be linked to the audit limitations that have been previously reported in the literature, and connected with the complaints of the organizations that experience difficulties with current ISO 9001 auditing. Auditing of conformance/performance, risk management and improvement in combination can be assured by upgrading, testing and validating this CAF. Originality/value: Utilizing the ISO 9001 quality audit in a way that helps organizations to audit performance, risk management and improvement in combination by changing the auditing approach from ISO 9001 elements to ISO 9001 principles and by learning from the experience of business excellence models implementers in development of the Performance measurement frameworks and in converting the concepts and principles into practice.